Quantifying Vulnerability to Poverty in the Future in the Local Region - Rio Triwahyu Saputra (Jurnal Ekonomi Pembangunan, 2021)
Poverty has always become a problem in an economic system, started from its detection to its eradication. So as happened in South OKU Regency, even its poverty level was the third lowest in the Province, but the human resources and economic system was not good enough. This led to a tendency that people in South OKU Regency just lived “as enough”, they were living above the poverty line, but so close to it. In the long term, this situation will become a serious problem. The poverty calculation method used by BPS Statistics Indonesia has limitedness as it does not include the aspects of social-economic and cannot calculate someone’s possibility to get into or out of poverty. This research aims to calculate the possibility of someone to become poor in the future and establish the solution to prevent it happens in South OKU Regency. With the vulnerability of expected poverty (VEP) analysis, it was known that there are 19,77 percent or 71.182 populations in South OKU Regency that are vulnerable to poverty. Based on the Decision Tree model created, the variables of per capita expenditure, asset ownership, and the number of household members can be used to classify households in South OKU regency by their poverty status. By detecting vulnerable to poverty households and helping them to sustain their welfare, will prevents the increase of the number of the poor in the future.